The Mexican Revolution in the revolutionary press of South America, 1910-1914. An American «Commune»? - Garrido González, Pablo (2026)
This study aims to examine how Magonism and the Mexican Revolution were received, spread, and understood among anarchist and revolutionary groups in the southern part of the Americas from 1910 to 1914. The research focuses on the anarchist and syndicalist movements in Argentina, Chile, and Peru. It seeks to identify the networks and interactions that contributed to the dissemination of Magonism in the region. Additionally, it describes the key translations and controversies, both local and international, related to the promotion, analysis, and challenges of the social revolution in Mexico.